Genetic diversity analysis of proso millet (Panicum miliaceum L.) germplasm resources based on phenotypic traits and SSR markers - Lv, Ziyang; Yang, Yixuan; Hou, Hanghang; Yang, Shangkun; Cui, Zhijia; Zhang, Xi; Li, Jing; Yuan, Yuhao; Liu, Minxuan; Feng, Baili (Frontiers in Plant Science, 2025)
IntroductionGermplasm resources are vital for food security and agricultural sustainability, providing the basis for seed industry innovation.MethodsIn the present study, 1,582 proso millet (Panicum miliaceum L.) germplasm resources, comprising landraces, cultivars, wild varieties, and foreign varieties, were sown in early June 2024 at the Yulin Minor Grain Comprehensive Experimental Demonstration Station. Subsequently, the genetic diversity was analyzed according to 14 agronomic, 5 yield, and 3 grain traits.ResultsSignificant phenotypic diversity was observed: agronomic trait diversity indices ranged from 0.15 to 2.10, with straw weight per plant showing the highest variation coefficients (60.03%). Yield traits exhibited diversity indices of 1.95-2.08 and variation coefficients of 14.94-37.37%. Grain traits had diversity indices exceeding 2, with the lowest variation coefficients (5.22-6.61%). Principal component analysis identified 4 key components, with tiller number and panicle length having the highest loading, leading to the selection of 10 superior germplasms. Cluster analysis grouped 1,582 samples into 5 categories, from which 147 representative germplasms were chosen. Then, 80 SSR primers were designed, 15 of which revealed polymorphism, confirming high genetic variation among these 147 germplasms. Varieties from Northwest China and Loess Plateau region showed the greater diversity.ConclusionThese findings provide a scientific foundation for the efficient utilization and breeding of proso millet germplasm resources.